2014
DOI: 10.7742/jksr.2014.8.2.89
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cervical Joint Mobilization on the Forward Head Posture and Neck Disability Indexes

Abstract: This paper tries to examine whether the application of joint mobilization to subjects who have the forward head posture due to malalignment in the cervical joint has influence on posture changes and functions in the cervical joint.The subjects were 39 students from G University in Gyeongsangbuk-do. The cervical joint mobilization was applied to 20 subjects and not to 19. The students with a cervical lordosis angle of 21° or less, an anterior weight bearing (AWB) of 15mm or greater, and a cervical extension ROM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…In a study by Oh 18 ) , the subjects were divided into a joint mobilization group, for which cervical SNAG mobilization was applied; a neuro-feedback group; and a control group, and changes in the neck postures after the treatments were compared. The results showed that joint mobilization had the most significant effect on postural improvements in the neck.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Oh 18 ) , the subjects were divided into a joint mobilization group, for which cervical SNAG mobilization was applied; a neuro-feedback group; and a control group, and changes in the neck postures after the treatments were compared. The results showed that joint mobilization had the most significant effect on postural improvements in the neck.…”
Section: Discussionmentioning
confidence: 99%
“…다양한 요소들이 관여하여 발생하는 만성 경항통 또한 후천적 만곡 소실과 무관하지 않으며, 매니퓰레이션, 관절가동술, 후두하근 이완 요법, 두 개경추 굴곡운동 등을 활용하여 치료하고 있다 [6][7][8] .…”
unclassified